Pheromone response elements are necessary and sufficient for basal and pheromone-induced transcription of the FUS1 gene of Saccharomyces cerevisiae. - Hagen, D C (1991)
The FUS1 gene of Saccharomyces cerevisiae is transcribed in a and alpha cells, not in a/alpha diploids, and its transcription increases dramatically when haploid cells are exposed to the appropriate mating pheromone. In addition, FUS1 transcription is absolutely dependent on STE4, STE5, STE7, STE11, and STE12, genes thought to encode components of the pheromone response pathway. We now have determined that the pheromone response element (PRE), which occurs in four copies within the FUS1 upstream region, functions as the FUS1 upstream activation sequence (UAS) and is responsible for all known aspects of FUS1 regulation. In particular, deletion of 55 bp that includes the PREs abolished all transcription, and a 139-bp fragment that includes the PREs conferred FUS1-like expression to a CYC1-lacZ reporter gene. Moreover, three or four copies of a synthetic PRE closely mimicked the activity conferred by the 139-bp fragment, and even a single copy of PRE conferred a trace of activity that was haploid specific and pheromone inducible. In the FUS1 promoter context, four copies of the synthetic PRE inserted at the site of the 55-bp deletion restored full FUS1 transcription. Sequences upstream and downstream from the PRE cluster were important for maximal PRE-directed expression but, by themselves, did not have UAS activity. Other yeast genes with PREs, e.g., STE2 and BAR1, are more modestly inducible and have additional UAS elements contributing to the overall activity. In the FUS1 promoter, the PREs apparently act alone to confer activity that is highly stimulated by pheromone.